PERSEPSI SISWA TERHADAP PENERAPAN PENDEKATAN SAINTIFIK PADA PEMBELAJARAN BIOLOGI KELAS X SMA NEGERI 12 PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine students' perceptions of the application of scientific approach to biology learning of class X SMA Negeri 12 Pekanbaru. This research was conducted at SMA Negeri 12 Pekanbaru in May - June 2017. The population in this research is all students of class X SMA Negeri 12 Pekanbaru Academic Year 2016/2017 consisting of class X MIA 1, X MIA 2, X MIA 3, X MIA 4 and X MIA 5. Research conducted is a descriptive research. The design of this study is descriptive qualitative by conducting questionnaires. Based on the result of the research, from the five indicators of the scientific approach the average of the lowest student perception is the indicator on communicate that is 3,4 with enough category, and the highest student perception is the indicator Observe and collect the information with good category that is 4.1 From the result Research known that Student Perception Against Application of Approach of Scientific In Learning of Biology Class X State Senior High School 12 Pekanbarut included in category Baik with average 3,8.Key words: Perception, Scientific Approach, Questionnaire